Identity - an Influential Factor in Modernization of Healthcare Systems in Hungary and Serbia - Kocsicska, Ivana; Varga-Kocsicska, Aleksandra (European Scientific Journal, ESJ, 2022)
The changing word and its economic trends are demanding adjustments in healthcare systems. The modernization of the healthcare appeared as global requirement, in connection with numerous changes in healthcare sector, including the financing and providing funds for unallayed services. Also, one of the crucial elements of the modernization is the development of the healthcare leadership and introducing elements of the shared leadership, in order to create an organizational culture, which can comply with the global changes resulting to economic and business transformations. Belonging to groups, families, and communities can empower leaders and increase commitment towards belonging. Through cultural humility, leaders are able to recognise and understand their own cultural self-identity and how this affects their leadership style. In this paper, the authors recognise that everyone has unique traditions, values, and beliefs (ethnic identity, language, religion, community, family ties), that everyone is connected to others, and that this greatly influences their leadership decisions. In order to provide a theoretical basis for the research, the authors aim to present a literature review of past research on identity as a factor influencing the modernization of healthcare (and leadership) in both Hungary and Serbia. Though there is a recognized need, opportunities for healthcare leadership development are limited both in Hungary and Serbia, including important limiting factors such as the fact that leaders are still sceptical about modern business and management elements in the healthcare sector. The ideal solution would be the combination of the early and mid-to-late career development and the integration of both the organizational and leadership development. This paper focuses on describing the healthcare systems in the two countries and understanding the factors that need to be highlighted in terms of their modernisation, both in the system and in relation to healthcare leadership.